Innovation in Services in the Tourist Sector: a Case Study in the Tents of “Praia do Futuro” (Fortaleza-Ceará-Brazil) - Sousa de Oliveira Saboia, Ana Cristina; Tavares, Jean Max; Riani Costa Perinotto, André (Anais Brasileiros de Estudos Turísticos, 2022)
This research aims to identify the main innovations implemented in the stalls of Praia do Futuro in Fortaleza (CE). The search for innovation of companies from different economic sectors aims to remain competitive, as well as meet customer expectations and needs in a satisfactory manner. In the tourism sector, innovation aims to provide the customer with a pleasant experience, stimulating the return to the tourist destination. The Praia do Futuro stalls, tourist attraction of Fortaleza destination, must be prepared to implement innovations that make its customers loyal through the quality and diversity of its services. This way, exploratory and descriptive research was carried out, with the application of a questionnaire in 31 stalls of the 60 existing stalls in Praia do Futuro. The results show that providing customer satisfaction is the most important reason to innovate, because the satisfied customer can attract new customers by disclosing the good service and, consequently, influence the increase in the profit of the stalls.